A new canine distemper virus lineage identified from red pandas in China. Issue 4 (12th November 2021) - Wang, Ruichen; Wang, Xiaohu; Zhai, Junqiong; Zhang, Pian; Irwin, David M.; Shen, Xuejuan; Chen, Wu; Shen, Yongyi
Abstract: Canine distemper virus (CDV) is a highly contagious virus that causes multi‐systemic, sub‐clinical to fatal diseases in a wide range of carnivore species. Based on the sequences of the haemagglutinin (H) gene, CDV strains have been classified into 18 major genetic lineages. In this study, we characterized the genomes of CDV isolated from the lungs of two dead red pandas in China. Histopathological and immunohistochemical analyses revealed damage due to viral infection in these lungs. The two strains showed a deep genetic distance from the other 18 recognized lineages (>4.6% at nucleotide level and >5.0% at amino acid level). The maximum clade credibility tree of the H‐ gene sequences showed that they belonged to an independent clade and had diverged a relatively long time ago from the Asia‐4 lineage (since 1884). These results suggest that the analyzed strains belong to a new CDV lineage, which we designate as Asia‐6. Our finding indicates that CDV infections in wildlife in China are complex and are a threat to endangered carnivores.